Osteomyelitis. Issue 2 (April 2015) - Bires, Angela Macci; Kerr, Bryan; George, Lynn
<x xml:space="preserve">Abstract</x> Diagnosis, early intervention, and treatment of patients who have an infection are the basic foundations of patient care. Early, appropriate interventions are associated with decreased patient morbidity and mortality. Diagnostic procedures with clinical information and laboratory results are integral in the assessment of inflammatory diseases and the prevention of sepsis. Some of the imaging modalities currently used for the assessment of inflammation include computed tomography, plain radiography, positron emission tomography, technetium Tc 99m bone scintigraphy, magnetic resonance imaging, and leukocyte scintigraphy. In the case of patients who exhibit signs of osteomyelitis, it is necessary to understand that acute and chronic conditions are not based on the duration of the disease but on the histopathologic features of the disease. Although several imaging modalities are considered appropriate, there is not one singular procedure that is considered ideal. Rather, it is a combination of procedures and various other clinical factors. This article addresses some of the advantages and disadvantages of the modalities, with a focus on molecular imaging and the assessment of osteomyelitis.